Simultaneous aberrations of single CDKN2A network components and a high Rb phosphorylation status can differentiate subgroups of primary cutaneous B-cell lymphomas - Kaune, Kjell M.; Neumann, Christine; Hallermann, Christian; Haller, Florian; Schön, Michael P.; Middel, Peter (Experimental Dermatology, 2011)
The cyclin-dependent kinase inhibitor 2A (CDKN2A) gene on chromosome 9p21 encodes p16 (INK4A), the inhibitor of the CDK4/retinoblastoma (Rb) cell proliferation pathway, as well as p14 (ARF), which controls p53-dependent pathways. Inactivation of p16 has previously been associated with the prognostically unfavourable primary cutaneous diffuse large B-cell lymphoma, leg type (PCLBCL, LT). In this work, we analysed 22 tumors [nine primary cutaneous follicle centre lymphomas (PCFCL), seven primary cutaneous marginal zone lymphomas (PCMZL) and six PCLBCL, LT] not only for alterations of the p16 gene but also for p14, p53 and Rb by fluorescence in situ hybridization (FISH) and immunohistochemistry. In most PCLBCL, LT (4/6) alterations of CDKN2A (two biallelic deletions, one monoallelic deletion and one trisomy 9) and in addition the highest frequency of deletions of p53 (3/6) and Rb (3/6) were detected. p16 was not expressed but very high levels of phosphorylated Rb, indicating a functional effect of genomic CDKN2A alterations on the protein level in PCLBCL, LT. Regarding the p14/p53 axis, PCLBCL, LT showed a variable expression. Neither PCFCL nor PCMZL showed alterations of CDKN2A and also deletions of p53 or Rb were extremely rare in these subtypes. Exclusively in PCMZL, p53 protein was consistently lacking. In conclusion, only PCLBCL, LT is characterized by a high frequency of aberrations of the CDKN2A network components in both important tumor suppressor pathways regulated by the CDKN2A gene. Moreover, PCLBCL, LT appears to be distinguishable from PCMZL not only by its level of p53 expression but also by its stage of Rb phosphorylation. The latter may also apply to a subgroup of PCFCL. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2025-03-24
Keywords: CDKN2A; Fluorescence in situ hybridization (FISH); p14; p16; p53; Primary cutaneous B-cell lymphoma; Rb